Implementation of Project Management Information Systems to Improve Efficiency and Accountability in Infrastructure Development - Irawaty (Global Writing Academica Researching & Publishing, 2025)
Government infrastructure development often faces various challenges in terms of implementation efficiency and budget management accountability. Projects involving many stakeholders usually experience coordination obstacles, slow reporting, and a lack of accountable documentation. Amidst the increasing complexity of projects and demands for public transparency, the use of information systems has become an unavoidable need. This study aims to examine how information system implementation strategies can improve the effectiveness of infrastructure project governance. The study was conducted with a qualitative approach and used data sources from previous research results. Data analysis was carried out thematically to describe the challenges and strategies for implementing information systems in government projects. The results of the study show that the success of implementation is greatly influenced by the adjustment of organizational workflows, human resource readiness, and managerial support. An integrated information system can accelerate reporting, increase performance visibility, and strengthen internal supervision. Therefore, the adoption of information systems needs to be accompanied by a comprehensive strategy in order to have a real impact on the efficiency and accountability of infrastructure projects.